Effects of Processing of Starter Diets on Performance, Nutrient Digestibility, Rumen Biochemical Parameters and Body Measurements of Brown Swiss Dairy Calves - Nejad, J. Ghassemi (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
In order to investigate the effect of physical forms of starter diets on performance, weaning age, nutrient digestibility and rumen biochemical factors, 24 female of neonatal Brown Swiss calves (average body weight of 39.5±1.2 kg) were randomly assigned to three treatments. Dietary treatments were mashed (MS), pelleted (PS), and texturized (TS) starter using 8 calves from birth till 90 days of age in each treatment. Diets were formulated to be iso-nitrogenous with 21% crude protein. Based on the experimental results, calves that received PS and TS diets, had significant higher average daily gain (ADG) than those receiving MS (p<0.01). Dry matter intake in calves fed PS and TS was greater than calves fed MS (p<0.05), but there was no significant difference in feed efficiency. Treatments had no effect on initiation of rumination. Weaning age of calves in MS was longer than the other two treatments (p<0.05). Crude protein and organic matter digestibility in MS treated calves were lower than other treatments (p<0.05). No differences were observed in neutral detergent fiber (NDF) and ash digestibility among treatments (p>0.05). Ruminal pH was higher (p<0.01) in MS than the other groups, but ruminal ammonia (g/dl) concentration was not different among the treatments. Body measurements such as body length, pin width, hip width, pin to hip length, size of metacarpus and metatarsus bones, hip height, wither height, stomach size and heart girth were not significantly different among the treatments. Overall, it is concluded that starter diets in the form of pellet and texture can improve performance in neonatal Brown Swiss calves compared to the mashed form.